GLOBAL LABOUR MARKET: MAIN TRENDS AND CHALLENGES - Андрій Конопленко; Роман Колесник (Економіка та суспільство)
Globalization, pandemics, and geopolitical upheavals have made large-scale changes in modern society, making the study of labor market development particularly relevant. The article examines the current state of the global labor market and identifies the leading trends and challenges in its development. The study employs methods of scientific abstraction, analysis and synthesis, logical generalization, historical-logical methods, and statistical analysis. The main trends in the development of the global labor market are analyzed, including digitalization and automation, hybrid forms of employment, the trend of work-life balance, changes in workforce demographics, the increasing role of soft skills and the growing role of outsourcing. The main risks facing the global labor market in the modern environment are summarized in this study, including job replacement through the development of artificial intelligence (AI) and automation processes, demographic changes, geopolitical crises, social challenges and inequality. The research has practical value as it offers insights into global labor market dynamics that can help policymakers, businesses, and educators develop strategies to address labor market challenges.